Zakat Pada Masa Pandemi Covid-19: A Systematic Literature Review - Ismail, Ismail; Wulan, Nur; Fitriani, Fitriani; Rahman, M.Saiful (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2024)
Covid-19 causes a wide range of economic, health, and social change problems globally. As a result, countries are no longer orderly in allocating development budgets because they are focused on tackling the covid-19 pandemic. This research aims to map the topics and research issues on zakat during the Covid-19 pandemic. The method used was Systematic Literature Review (SLR) with analysis using the Vosviewer application. The 31 articles reviewed were sourced from the Scopus database from 2020 to 2023. The results revealed that there were 31 researchers who examined zakat during the Covid-19 pandemic. Indonesia is the country with the highest number of studies on zakat. This was triggered by the massive utilisation of zakat funds for covid-19 prevention after the issuance of the fatwa by the Indonesian Ulema Council. At the zakat collection stage, the topic of Person and Community is an issue that is widely researched because of its influence on zakat collection. The Model topic becomes an important issue at the zakat distribution stage which can be channelled through Business Capital, Revolving Funds, and scholarships. For the latest topic, Lazismu and Zakatech are the main issues. Lazismu is one of the zakat institutions that massively overcomes the impact of Covid-19. Meanwhile, the digitalisation of zakat management is important to be applied for the future. While Lazismu and Model topics are also part of the dominant topics.